Reconstruction of the Relationship between Islam and Politics from a Transdisciplinary Perspective - Ahmad Damanhuri; Nurkholis Sofwan; Hudallah Hudallah (Lentera Demokrasi: Jurnal Ilmu Sosial, Politik, Hukum, Ekonomi dan Pemerintahan, 2025)
The relationship between Islam and politics has evolved across various historical periods, ranging from the classical, colonial, to post-colonial eras. During the colonial period, organizations such as Sarekat Islam, Muhammadiyah, and Nahdlatul Ulama in Indonesia formulated forms of resistance and socio-political reform grounded in Islamic principles. Meanwhile, Middle Eastern thinkers such as Jamal al-Din al-Afghani and Muhammad Abduh led reform movements that sought to harmonize Islamic values with the demands of modernity. This study aims to understand the complex relationship between Islam and politics through a holistic and transdisciplinary approach. In the context of globalization, modern values such as democracy and human rights often interact with Islamic principles, creating the need for deeper dialogue. This research employs a qualitative approach and literature study, utilizing relevant scholarly sources to establish a strong theoretical foundation. The findings indicate that political understanding in Islam encompasses not only structures of power but also ethical and moral values that function to achieve justice and the common good. A transdisciplinary approach enables the integration of various fields of study—including sociology, theology, and political science—to generate a more comprehensive understanding of the dynamics of Islam–politics relations. This study also highlights the importance of social and cultural contexts in the application of Islamic principles within the political sphere, as well as the challenges of reconciling traditional values with modern demands. Thus, this research contributes to the reconstruction of Islamic political thought that is adaptive and inclusive, capable of accommodating contemporary changes without compromising the essential teachings of Islam.